x+2n=15n+23

Simple and best practice solution for x+2n=15n+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+2n=15n+23 equation:


Simplifying
x + 2n = 15n + 23

Reorder the terms:
2n + x = 15n + 23

Reorder the terms:
2n + x = 23 + 15n

Solving
2n + x = 23 + 15n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-15n' to each side of the equation.
2n + -15n + x = 23 + 15n + -15n

Combine like terms: 2n + -15n = -13n
-13n + x = 23 + 15n + -15n

Combine like terms: 15n + -15n = 0
-13n + x = 23 + 0
-13n + x = 23

Add '-1x' to each side of the equation.
-13n + x + -1x = 23 + -1x

Combine like terms: x + -1x = 0
-13n + 0 = 23 + -1x
-13n = 23 + -1x

Divide each side by '-13'.
n = -1.769230769 + 0.07692307692x

Simplifying
n = -1.769230769 + 0.07692307692x

See similar equations:

| 3a+13=9a | | 13-9x=133-37x | | x+2n=5n+23 | | 3x+(2/5)=4x+(4/5) | | (8x+12)=((5x-5)2) | | 6x-7=79-2x | | 9+4x=18x | | 9y-10=5y-54 | | 6x^4-12x^2= | | (3-4)+4*3*-3= | | 72x^2+56x/9x-7 | | 7(2x-8)-6=14x-62 | | 4(m-2)-7+2m=6(m+5) | | (8x+12)=(5x-5) | | 3z+7=35 | | 6(1/3)= | | 0*X=5 | | 8r+-5=51 | | 16+-9-2(4*3*1/2)= | | 8/3-2i | | -10+2m=8 | | 90+.4x=X | | 16+x^2=49 | | 5/4a+2=22 | | 8/(3-2i) | | 9y+-10=5y+54 | | -4(3y-10)+2(2y+9)= | | 4/3p=16 | | h(t)=5t^2-30t+45 | | 3/2n=15 | | 2(-3)+16-(3+4)= | | B=900(1+.02) |

Equations solver categories